169k views
1 vote
What the answer 2(23 + a) = 34

2 Answers

5 votes

Answer:

a = -6

Explanation:

2(23 + a) = 34,

multiply the 2 into the bracket of (23 + a)

then it will become,

46 + 2a = 34

shift the numbers with unknown to one side,

2a = 34 — 46

so,

a = -12/2

at last,

a = -6

User Eythort
by
5.6k points
5 votes

Answer

-6

Explanation:

2(23+a)=34

(2)(23)+(2)(a)=34(Distribute)

46+2a=34

2a+46=34

Step 2: Subtract 46 from both sides.

2a+46−46=34−46

2a=−12

Step 3: Divide both sides by 2.

2a

2

=

−12

2

a=−6

User Kemat Rochi
by
5.9k points